Targetable Alterations in Adult Patients With Soft-Tissue Sarcomas: Insights for Personalized Therapy - Lucchesi, Carlo (JAMA Oncol, 2018)
IMPORTANCE: Patients with advanced soft-tissue sarcomas (STS) have a median overall survival of less than 18 months. Identification of molecular abnormalities for which targeted therapies are available or can be developed is critical for improving patient outcomes. OBJECTIVE: To characterize targetable genomic alterations (GAs) in patients with STS. DESIGN, SETTING, AND PARTICIPANTS: This cross-sectional study of next-generation sequencing results from 584 patients with STS included in the AACR GENIE Database. MAIN OUTCOMES AND MEASURES: Presence of targetable GAs in STS. RESULTS: Of 584 patients included in the analysis, 294 (50.3%) were men and 290 (49.7%) were women, with a median age of 56 years (range, 18-89 years). There were 331 (57%) patients with complex genomics sarcomas, 144 (25%) with translocation-related sarcomas, and 112 (18%) with other sarcomas (inactivating mutation, simple amplicon). A total of 2697 alterations were identified in 451 genes (1154 substitutions, 765 gene amplifications, 364 short indels and splicing variants, 346 gene homozygous deletions, and 68 gene rearrangements) with a median of 4 (1-53) per case. In order of frequency, the 20 genes most often altered were: TP53, MDM2, CDK4, RB1, ATRX, CDKN2A, PTEN, NF1, CDKN2B, KMT2D, GLI1, ATM, TERT, PI3KCA, NOTCH1, MAP2K4, ERBB4, ARID1A, TSC2, and TNFAIP3. At least 1 targetable GA was found in 239 cases (41%) with a statistically significant higher number in other and complex genomics sarcomas than in translocation-related sarcomas (respectively other: n=89, 82%, complex: n = 131, 40%, translocation: n = 19, 13%; χ(2) test, P < .001). CONCLUSIONS AND RELEVANCE: Up to 41% of STS harbored at least 1 clinically relevant GA with potential to influence and personalize therapy. Comprehensive genomic profiling can identify novel treatment paradigms to address the limited options and poor prognoses of patients with STS.